2013
DOI: 10.1186/1678-9199-19-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of antivenoms for the treatment of envenomation by Elapidae snakes in Guinea, Sub-Saharan Africa

Abstract: BackgroundIn Guinea Elapids are responsible for 20% of envenomations. The associated case fatality rate (CFR) ranged 15-27%, irrespective of treatment.ResultsWe studied 77 neurotoxic envenomations divided in 3 groups: a set of patients that received only traditional or symptomatic treatments, and two other groups that received either 2 or 4 initial vials of Antivipmyn® Africa renewed as necessary. CFR was 27.3%, 15.4% and 17.6%, respectively. Although antivenom treatment was likely to reduce CFR, it didn’t see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…For example, many patients preferred to consult a traditional healer as indicated by a previous study in the southwest of Burkina Faso in 2002 [ 7 ]. In addition, several patients bitten by Elapidae snakes die before reaching health centers due to a long delay between the bite and admission to hospitals [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, many patients preferred to consult a traditional healer as indicated by a previous study in the southwest of Burkina Faso in 2002 [ 7 ]. In addition, several patients bitten by Elapidae snakes die before reaching health centers due to a long delay between the bite and admission to hospitals [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of death from carpet viper and other snakebites among untreated victims was previously reported at 8.1–15.83% and 5–27.3% respectively [ 9 , 10 , 38 , 39 , 40 , 41 , 42 ] although these were varied in sensitivity analyses. When data on antivenom effectiveness was available for a given country, it was applied for that country.…”
Section: Methodsmentioning
confidence: 99%
“…Results from the meta-analysis suggested that an effective antivenom has a 75% (95% confidence interval: 55–86%) effectiveness in averting mortality from carpet viper bites [ 22 ]. Since the meta-analysis included studies wherein polyspecific antivenoms were used, these estimates of effectiveness were applied against non-carpet viper deaths except in Benin and Guinea-Conakry, where country-level effectiveness data exists for Antivipmyn antivenom against non-carpet viper (elapid) deaths, reported at 43.6% (0–80.5%) ( Table 1 ) [ 42 ]. However, in a scenario analysis antivenoms were assumed to be ineffective (0%) against non-carpet viper envenoming.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors suggested that it is due to the failure of antibodies to bind to the receptor-bound toxins which subsequently prevents the formation of toxin-antibody complex (Balde et al, 2013). Other suggested that it could be due to pharmacokinetic constraints -neurotoxins are present abundantly in extravascular compartment where their target receptors are located, whereas antibodies are likely to circulate in vascular compartment as their distribution to the extravascular compartment is restrained by their large molecular size (Gutierrez et al, 2003).…”
Section: The Issue Of Low Potency Of Npav Against Asiatic Cobra Venomsmentioning
confidence: 99%